2021
DOI: 10.1016/j.breast.2021.07.017
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of palbociclib in patients with estrogen receptor–positive/human epidermal growth factor receptor 2–negative advanced breast cancer with preexisting conditions: A post hoc analysis of PALOMA-2

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 12 publications
1
6
0
1
Order By: Relevance
“…While not all patients started palbociclib at the recommended dose of 125 mg/day and 37.9% had their dose reduced, studies have shown that dose reduction does not adversely affect PFS. Clifton et al 32 reported more dose reductions in older adults (aged >65.0 years); however, they found rwPFS to be longer (but not significantly so after adjustment) for patients who experienced dose reductions; 32 while patients with pre‐existing conditions often experienced dose reductions, they still obtained a PFS benefit 33 . In a real‐world study of patients receiving palbociclib with fulvestrant in the 2L or greater treatment setting, median rwPFS did not differ among patients with neutropenia‐related dose reductions and interruptions and those without dose modifications 34 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While not all patients started palbociclib at the recommended dose of 125 mg/day and 37.9% had their dose reduced, studies have shown that dose reduction does not adversely affect PFS. Clifton et al 32 reported more dose reductions in older adults (aged >65.0 years); however, they found rwPFS to be longer (but not significantly so after adjustment) for patients who experienced dose reductions; 32 while patients with pre‐existing conditions often experienced dose reductions, they still obtained a PFS benefit 33 . In a real‐world study of patients receiving palbociclib with fulvestrant in the 2L or greater treatment setting, median rwPFS did not differ among patients with neutropenia‐related dose reductions and interruptions and those without dose modifications 34 .…”
Section: Discussionmentioning
confidence: 99%
“…Clifton et al 32 reported more dose reductions in older adults (aged >65.0 years); however, they found rwPFS to be longer (but not significantly so after adjustment) for patients who experienced dose reductions; 32 while patients with pre-existing conditions often experienced dose reductions, they still obtained a PFS benefit. 33 In a real-world study of patients receiving palbociclib with fulvestrant in the 2L or greater treatment setting, median rwPFS did not differ among patients with neutropenia-related dose reductions and interruptions and those without dose modifications. 34 While these studies report no adverse effect of lower doses, at least one study observed that patients starting palbociclib at the recommended dose had a higher rwPFS and real-world best tumor responses than the small proportion of patients who started at lower doses.…”
Section: Probability (%)mentioning
confidence: 91%
“…In a pooled analysis of the PALOMA 1,2 and 3 studies, median progression-free survival was signi cantly improved in patients aged 65-74 years (hazard ratio [HR], 0.66; 95% con dence interval [CI], 0.45-0.97; P = 0.016) and ≥ 75 years (HR, 0.31; 95% CI, 0.16-0.61; P < 0.001) receiving palbociclib plus letrozole and in patients aged 65-74 years (HR, 0.27; 95% CI, 0.16-0.48; P < 0.001) receiving palbociclib plus fulvestrant (24). A consistent bene t of CDK4/6i in combination with AI was observed across all subgroups examined in the P-REALITY and P-REALITY-X studies (older patient groups and among patients with and without visceral metastases or bone-only disease) (14,28) and also that patients with different comorbidities continue to bene t from palbociclib (29).…”
Section: Discussionmentioning
confidence: 90%
“…Therefore, the level of HER2 expression may also have an impact on the outcome of individuals with HR + breast cancer. Prior studies [ 27 29 ] have also evinced that HER2 non-expression or low-expression has a specific influence on the survival of HR + breast cancer, although not statistically significant. This phenomenon deserves further investigation in the future and may be incorporated into predictive models to more accurately assess the survival prognosis of HR + /HER2- MBC.…”
Section: Discussionmentioning
confidence: 99%